INTELLECTUAL STRUCTURE OF CARBON EMISSION AND CLIMATE CHANGE IN SUSTAINABILITY REPORTING: A BIBLIOMETRIC ANALYSIS - Richatul Jannah; Fitrarena Widhi Rizkyana; Risanda Alirastra Budiantoro (Jurnal Akuntansi AKTIVA, 2023)
The research topic of carbon emission and climate change in sustainability reporting were published in the publications used in this study are from 1999 to January 2023. The data discusses intellectual structure of carbon emission and climate change in sustainability reporting in this study came from 96 sources in the form of 79 articles, 2 books, 11 book chapters, 18 conference papers, 1 note, and 11 reviews. R-Biblioshiny in this research was for analysis and data visualization. Furthermore, additional analysis was also carried out using the Vos Viewer. From the network visualization, research related to the influence of carbon emission and climate change has not been done much and works analyzing these influences are still potential recently.The findings of this study serve as a reference and provide direction for future researchers and provide mapping related to carbon emission and climate change in sustainability reporting. More research in this field and works analyzing these influences are needed moreover about future environmental and sustainability impact. The findings of this study serve as a reference and provide direction for future researchers and provide mapping related to carbon emission and climate change in sustainability reporting. More research on the influence of carbon emission and climate change in this field and works analyzing these influences are needed moreover about future environmental and sustainability impact in accounting scope.This research topic still has many opportunities to be carried out within the scope of the accounting and finance journal. This research is expected to be able to provide references, especially for Indonesian Researchers who will conduct international publications on similar topics. Limitations this research is mostly based on data processing keywords that are not accompanied by reasons for selecting these keywords. In addition, the data used is limited to articles published on Scopus. Indonesian Researchers are advised to collaborate with more researchers from other countries with very productive researchers related to this topic. Opportunities for international publications will also be bigger if the publication targets journals that have published many works from Indonesian Researchers.